Google search based sentiment indexes. Issue 3 (September 2020) - Brochado, Ana
Abstract: This study sought to confirm whether Internet search based data have the potential both to reveal populations' underlying beliefs directly and to affect stock markets of countries – in this case, Portugal. Based on the Internet search volume of several queries related to household concerns, we constructed two Google-based sentiment measures – a Positive Sentiment Index and a Negative Sentiment Index – encompassing both positive and negative search terms. The results reveal that both measures are correlated with aggregate stock market returns, trading volume, and abnormal trading volume. Also, positive sentiment has a stronger impact on these stock market variables than negative sentiment. Further, the proposed sentiment measures are significantly useful when making short-term predictions of market returns and volume.